Family Financial Management Training at The Puspa Forum Mojokerto City - Dwi Dewianawati; Mila Hariani; Erry Setiawan; Elly Joenarni; Yusuf Rahman Al Hakim; Poppy Meilina Dian Hastuti; Sari Rahayu Rahayu (PT FORMOSA CENDEKIA GLOBAL, 2023)
Community service includes efforts to make positive contributions to a particular community with the aim of improving their quality of life and welfare. One of the problems that many families often face is a lack of understanding and skills in financial management, which can have a negative impact on financial stability and family well-being. Therefore, this community service aims to provide family financial management training to the mothers of the Mojokerto City Puspa Forum. This training is designed to provide basic knowledge about financial management to participants. This training methodology involves community service activities carried out in Mergelo Village, Balongsari, Magersari District, Mojokerto City which was held on Saturday, September 16 2023, at the Mojokerto City P3A Social Service Office. Implementation of activities is carried out in three stages, namely the preparation stage, work program stage, and reporting stage. The targets of this community service activity are the village residents of Forum Puspa. The expected result of this community service is an increase in participants' understanding of personal financial management and their ability to manage family finances more effectively. In this way, it is hoped that they will be able to increase their financial stability, reduce their debt burden, and improve their overall quality of life.